Keystone flap: Suitable option for coverage of soft tissue defect over Tendo Achilles following open repair - Islam, Md Salek Bin; Rahman, Md Moshidur; Islam, Md Azizul; Uddin, Md Zalal; Khan, Md Noazesh (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Wound complications are not uncommon following operative Tendo Achilles repair. Patients presented in Plastic surgery department with soft tissue defect on Tendo achilles region with exposed Tendon. The paucity of tissue and poor blood circulation are main challenges for the reconstructive surgeon. The study aimed to evaluate the Keystone flap for soft tissue coverage of defects following Tendo achilles repair. Methods: This prospective study was conducted on January 2021 to December 2022 in Plastic surgery department of Rajshahi Medical College Hospital and all 12 cases were done by single surgeon. All patients had history of repair for ruptured Tendo Achilles and were presented with defect over Tendo achilles near or at its insertion, where the defect length was larger than width. Keystone flap type IIA was done for each defect. Results: Mean age of the study patients was 43.42 ±9.79 years. The highest dimension of wound was 36.80 (8 X 4.6) cm2 and flap was 66 (10 X 6.6) cm2. The range of advancement of flap was 3- 4.6 cm (mean: 3.43 ±0.54 cm) in transverse axis of leg. Mean duration of operative time was 53.58± 10.06 minutes. Follow up period was 3 months to measure outcome the flap. Conclusion: The keystone flap has high survivability rate with low complications rate providing with good functional outcome of joint. So, keystone flap is a suitable option for coverage of soft tissue defects following operative Tendo Achilles repair. J Bangladesh Coll Phys Surg 2024; 42: 155-160